If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14 + -10x = 8x + 23 Reorder the terms: -14 + -10x = 23 + 8x Solving -14 + -10x = 23 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -14 + -10x + -8x = 23 + 8x + -8x Combine like terms: -10x + -8x = -18x -14 + -18x = 23 + 8x + -8x Combine like terms: 8x + -8x = 0 -14 + -18x = 23 + 0 -14 + -18x = 23 Add '14' to each side of the equation. -14 + 14 + -18x = 23 + 14 Combine like terms: -14 + 14 = 0 0 + -18x = 23 + 14 -18x = 23 + 14 Combine like terms: 23 + 14 = 37 -18x = 37 Divide each side by '-18'. x = -2.055555556 Simplifying x = -2.055555556
| 2x-1=12-81 | | 5x-25=35 | | 2(5x-4)=4(x+7) | | (5x+6)(x-1)-(2x-5x+3)=0 | | X^3=36 | | 2n^3+7=2n^5 | | 140-7x=38x+15 | | 5n+7=27 | | (n-6)*2=4 | | (n-6)*10=70 | | 65=-4(5b+3) | | 108-3x=4x+17 | | 14-6x=6-8x | | 7(2y-3)=28 | | 8x^3+4x^2-34x+15=0 | | -3(4-2w)=10 | | 3(4-3s)=34 | | 3g+15=5g-3 | | 9x+23=3x+197 | | -3(4-2n)=19 | | -3(4-2)=19 | | 2x+3=2(2x+7) | | 5x+26=15x-64 | | x*x=x | | x+2x-3x+4x-5x=-5 | | 2x^2-4kx+k=0 | | 9x^4-3x^2+1= | | 3x*2+5x+3=0 | | 2(x+1)-(x+2)=3 | | 2(x+1)-(x-2)=3 | | 72-3x=6x+24 | | 25xsomthing=105 |